Roggendorf, Joseph (ed.), Studies in Japanese Culture, Tradition and Experiment. Sophia University Press, Tokio, 1965. (Monumenta Nipponica Monographs, núm. 23.) 276 pp. - C. F. (El Colegio de México, A.C., 1969)
-